2013
DOI: 10.1021/jp4018794
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Size Exclusion Chromatographic NMR of Sunset Yellow FCF in Solution

Abstract: Size-exclusion chromatographic NMR is the application of size-exclusion chromatographic media to modify the observed diffusion properties of analyte molecules, as measured by diffusion ordered spectroscopy. This Article demonstrates the application of this method to isotropic solutions of sunset yellow, which are known to be formed of large, noncovalent aggregates. The results show a partitioning effect of the aggregates between in-pore and free solution environments, which is explained by size-exclusion behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Once the assemblies grow beyond a certain size, they can no longer enter the pores, therefore a partitioning between smaller aggregates within the pores and larger assemblies in free solution is established 48 .…”
Section: Use Of Chromatographic Supportsmentioning
confidence: 99%
“…Once the assemblies grow beyond a certain size, they can no longer enter the pores, therefore a partitioning between smaller aggregates within the pores and larger assemblies in free solution is established 48 .…”
Section: Use Of Chromatographic Supportsmentioning
confidence: 99%
“…Recently, we have extended the concept of chromatographic NMR to the use of size‐exclusion stationary phases . These phases comprise a porous material, typically based on cross‐linked dextran, with pore sizes on the order of 10–100 nm.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the observed changes in diffusion properties of a series of polymer molecular weight reference standards is consistent with size‐exclusion behaviour, in which smaller polymers show greater retardation in their diffusion than larger polymers . These systems have also been used to investigate aggregating systems, with assemblies of the azo‐dye sunset yellow partitioning between the pores in the stationary phase and the free solution surrounding the particles, depending on the overall aggregate size . In both cases, the large size of the analyte molecules or assemblies means that the addition of the stationary phase causes only minor additional line broadening …”
Section: Introductionmentioning
confidence: 99%
“…[15] These systems have also been used to investigate aggregating systems, with assemblies of the azo-dye sunset yellow partitioning between the pores in the stationary phase and the free solution surrounding the particles, depending on the overall aggregate size. [16] In both cases, the large size of the analyte molecules or assemblies means that the addition of the stationary phase causes only minor additional line broadening. [15,16] In this paper, we demonstrate extending of the range of applicability of in situ size-exclusion chromatographic NMR to polymer mixtures.…”
Section: Introductionmentioning
confidence: 99%